(untitled) (Jurnal Teknologi (Sciences & Engineering), 2024)
An attempt has been made to develop sustainable and low-cost geopolymer interlocking bricks using the binders namely Ground Granulated Blast Furnace Slag (GGBS) and fly ash by activating them with hydroxides and silicates of sodium. M-Sand is used in combination with waste glass as fine aggregates. Seven mix ratios adopted are : Bricks with 100% M-Sand, 90% M-Sand and 10% waste glass, 80% M-Sand and 20% waste glass, 70% M-Sand and 30% waste glass, 60% M-Sand and 40% waste glass, 50% M-Sand and 50% waste glass and 40% M-Sand and 60% waste glass. Physical tests were conducted for all the materials used. In total, eighty-four interlocking bricks of size 300 mm x 200mm x 125mm were cast and the bricks were kept in room temperature for 28 days. Interlocking bricks were then tested for density, compressive strength and water absorption. Prisms of length 600 mm, height 375 mm and width 200 mm were constructed using three layers of interlocking bricks and subjected to compressive load. Interlocking bricks with 70% M-Sand and 30% Waste glass exhibited maximum compressive strength and low water absorption. Prisms with 70% M-Sand and 30% waste glass has maximum ultimate load carrying capacity and energy Absorption.